2023
DOI: 10.1093/brain/awad064
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dopamine release in Parkinson’s disease

Abstract: Parkinson’s disease is the second most common neurodegenerative disease and yet the early pathophysiological events of the condition and sequences of dysfunction remain unclear. The loss of dopaminergic neurons and reduced levels of striatal dopamine are descriptions used interchangeably as underlying the motor deficits in Parkinson’s Disease. However, decades of research suggest that dopamine release deficits in Parkinson’s Disease do not occur only after cell death, but that there is dysfunction or dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 155 publications
0
23
0
Order By: Relevance
“…The accumulation and deposition of Lewy bodies are closely related to the increase in the death level of DA neurons. 69 α-SYN is the main protein in Lewy bodies. The accumulation of α-SYN in PD patients is higher than that in healthy individuals, and this phenomenon is also observed in MPTP-induced animal models such as monkey, mouse, and silkworm.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation and deposition of Lewy bodies are closely related to the increase in the death level of DA neurons. 69 α-SYN is the main protein in Lewy bodies. The accumulation of α-SYN in PD patients is higher than that in healthy individuals, and this phenomenon is also observed in MPTP-induced animal models such as monkey, mouse, and silkworm.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 As the most abundant catecholamine neurotransmitter in the brain, dopamine regulates the central nervous system. The abnormal concentration of dopamine can cause neurological disorders such as Parkinson's disease, 8,9 schizophrenia, 10 and Tourette's syndrome. 11 Fascinatingly, it has been shown that uric acid has a protective effect on dopamine neurons in Parkinson's disease and that uric acid levels affect the course of Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…A delicate dynamic balance is maintained through production and excretion. , Once the balance is disturbed, it can lead to a variety of diseases, such as hyperuricemia, gout, , and cardiovascular system diseases. , As the most abundant catecholamine neurotransmitter in the brain, dopamine regulates the central nervous system. The abnormal concentration of dopamine can cause neurological disorders such as Parkinson’s disease, , schizophrenia, and Tourette’s syndrome …”
Section: Introductionmentioning
confidence: 99%
“…1,2 One of the most prominent pathological hallmarks of PD is the loss of dopaminergic neurons in the substantia nigra, 3 resulting in the deficiency of dopamine in the striatum. 4 Dopamine transporter imaging using single-photon emission computed tomography (DAT-SPECT) is one of the most highly developed supplementary assessments for PD, which is utilized to indirectly measure DAT availability in straitum. 5,6 Striatal binding ratio (SBR) in striatum measured by DAT-SPECT has been demonstrated to be associated with motor manifestations, including rigidity, 7,8 resting tremor, 9 and bradykinesia.…”
Section: Introductionmentioning
confidence: 99%